pH-induced conformational changes in the selectivity filter of a potassium channel lead to alterations in its selectivity and permeation properties - Coll-Díez, Carlos; Giudici, Ana Marcela; Potenza, Alberto; González-Ros, José Manuel; Poveda, José Antonio (Frontiers in Pharmacology, 2025)
The Selectivity Filter (SF) in tetrameric K+ channels, has a highly conserved sequence, TVGYG, at the extracellular entry to the channel pore region. There, the backbone carbonyl oxygens from the SF residues, create a stack of K+ binding sites where dehydrated K+ binds to induce a conductive conformation of the SF. This increases intersubunit interactions and confers a higher stability to the channel against thermal denaturation. Indeed, the fit of dehydrated K+ to its binding sites is fundamental to define K+ selectivity, an important feature of these channels. Nonetheless, the SF conformation can be modified by different effector molecules. Such conformational plasticity opposes selectivity, as the SF departs from the “induced-fit” conformation required for K+ recognition. Here we studied the KirBac1.1 channel, a prokaryotic analog of inwardly rectifying K+ channels, confronted to permeant (K+) and non-permeant (Na+) cations. This channel is pH-dependent and transits from the open state at neutral pH to the closed state at acidic pH. KirBac1.1 has the orthodox TVGYG sequence at the SF and thus, its behavior should resemble that of K+-selective channels. However, we found that when at neutral pH, KirBac1.1 is only partly K+ selective and permeates this ion causing the characteristic “induced-fit” phenomenon in the SF conformation. However, it also conducts Na+ with a mechanism of ion passage reminiscent of Na+ channels, i.e., through a wide-open pore, without increasing intersubunit interactions within the tetrameric channel. Conversely, when at acidic pH, the channel completely loses selectivity and conducts both K+ and Na+ similarly, increasing intersubunit interactions through an apparent “induced-fit”-like mechanism for the two ions. These observations underline that KirBac1.1 SF is able to adopt different conformations leading to changes in selectivity and in the mechanism of ion passage.